Estimation of the size of a molecules and Avogadro's number - Perez, Erlinda M. (1972)
The purpose of the study is to know the conditions that will give a more accurate measurement of the size of an oleic acid molecule and Avogadro's number using the monomolecular layer method modified by Demchik and Demchik. In the monomolecular layer method, the cylinder is utilized as the shape and the diameter of the cross section of the cylinder is taken by spreading oleic acid in dilute HCL.